Engaging Citizens and Transforming Designers: Analysis of a Campus-Community Partnership Through the Lens of Children's Rights to Participation - Victoria Derr; Laura Healey Malinin; Meredith Banasiak (The University of Alabama, 2022)
While an engaged citizenry is often the goal of community service learning, the rights of children to be active agents in this process are largely considered in a separate academic literature. Yet community service learning and children's participation share much in their goals and approaches to engagement. This paper analyzes a campus-community partnership between undergraduate environmental design and middle school applied science students. The partnership began as a way to promote participatory design processes for the redesign of a middle school and evolved to a proactive co-design program. We describe the goals and approaches to service-learning employed through the partnership, and critique the evolution of the program through the realm of a participation model that has emerged from three decades of children's participation research. By analyzing a campus-community partnership through this framework, we hope to deepen the discourse on approaches to and evaluation of successful service-learning programs.